A treasury of Spurgeon on the life and work of our Lord ; v. 3 - Spurgeon, Charles Haddon, 1834-1892 (Grand Rapids, MI Baker, 1979)
Contents : v. 3 : The parables of our Lord
Keywords: Jesus Christ -- parables